Analysis of Urban Green Space and Vegetation Density on Air Quality in West Java - Novaldi Laudi Angrianto; Christian Soleman Imburi (Westscience Press, 2026)
This study examines the influence of urban green spaces and vegetation density on air quality in West Java by incorporating public perceptions as a key analytical component. A quantitative approach was employed using data collected from 125 respondents through a structured questionnaire based on a Likert scale. The data were analyzed using IBM SPSS Statistics 25, including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that urban green spaces have a positive and significant effect on air quality, while vegetation density also shows a positive and significant influence. Simultaneously, both variables significantly affect air quality, as confirmed by the F-test. The coefficient of determination reveals that 41.1% of the variation in perceived air quality is explained by urban green spaces and vegetation density. These findings highlight the importance of integrating green infrastructure and vegetation management into urban planning policies. Enhancing both the quantity and quality of green spaces can significantly improve environmental conditions and public well-being. This study provides practical implications for policymakers to develop sustainable urban strategies that align with community perceptions and environmental needs.